Membangun Usaha Kreatif, Inovatif dan Bermanfaat Melalui Penerapan Kewirausahaan Sosial - Mawaddah Tun'nisa; Audia Amanda Tarigan; Mulia Ardiansah Harahap (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
Entrepreneurship is the ability to be creative and innovative; Therefore, pay attention to opportunities and always be open to any positive changes and improvements. who have the ability to sustain the business. A successful business has value and benefits. Where this can be done by using the application of the concept of social entrepreneurship. Various clans started by refining the concept of social media business acumen as an innovative solution to address social dynamics. The goal of social work is to be honest. shifting social direction towards something better or more positive and solving social problems to achieve important things. Entrepreneurship is a creative and innovative ability, being open-minded and always seeing opportunities for every success and positive change that has the ability to sustain a business. A successful business has value and benefits, which can be done by applying the concept of social entrepreneurship in various clans, starting with perfecting the concept of business acumen.